PELAKSANAAN PEMBINAAN PERILAKU NARAPIDANA DI RUMAH TAHANAN NEGARA KELAS IIB PEMALANG (Civic Education Program, Universitas Negeri Semarang, 2022)
The guidance carried out at the Class IIB Pemalang Rutan aims to prepare inmates so that later they can return and be accepted by the community. The problems of this research are (1) how is the implementation of behavioral development carried out by prisoners in the Class IIB Pemalang Rutan (2) what obstacles are faced by Rutan officers in fostering prisoners (3) what efforts are made to overcome obstacles in fostering the behavior of prisoners in the Class IIB Pemalang Rutan. The results of this study indicate that (1) behavioral development carried out at the Class IIB Pemalang Rutan includes religious development which is carried out almost every day, fostering national and state awareness through flag ceremonies which are carried out every Monday, legal awareness building and skills development, (2 ) Obstacles in the implementation of behavioral development include the lack of prison officers, inadequate facilities and infrastructure, and overcapacity of inmates, (3) efforts made to overcome obstacles in fostering are proposing additional prison officers, proposing additional facilities and infrastructure, and transferring prisoners to Correctional Institution.